Factors influencing postpartum women's willingness to participate in a preventive pelvic floor muscle training program: a web-based survey. (December 2015) - Moossdorff-Steinhauser, Heidi F.A.; Albers-Heitner, Pytha; Weemhoff, Mirjam; Spaanderman, Marc E.A.; Nieman, Fred H.M.; Berghmans, Bary
Abstract: Objective: Pregnancy and delivery are the most prominent risk factors for the onset of pelvic floor injuries and – later-on – urinary incontinence. Supervised pelvic floor muscle training during and after pregnancy is proven effective for the prevention of urinary incontinence on the short term. However, only a minority of women do participate in preventive pelvic floor muscle training programs. Our aim was to analyze willingness to participate (WTP) in an intensive preventive pelvic floor muscle training (PFMT) program and influencing factors, from the perspective of postpartum women, for participation. Study design: We included 169 three-month postpartum women in a web-based survey in the Netherlands. Demographic and clinical characteristics, knowledge and experience with PFMT and preconditions for actual WTP were assessed. Main outcome measures were frequencies and percentages for categorical data. Cross tabulations were used to explore the relationship between WTP and various independent categorical variables. A linear regression analysis was done to analyze which variables are associated with WTP. Results: A response rate of 64% ( n = 169) was achieved. 31% of the women was WTP, 41% was hesitating, 12% already participated in PFMT and 15% was not interested (at all). No statistically significant association was found between WTP and risk or prognostic pelvic floor dysfunction factors. Women already having symptoms of pelvic floor dysfunction such as incontinence and pelvic organ prolapse symptoms were more WTP ( p = 0.010, p = 0.001, respectively) as were women perceiving better general health ( p < 0.001). Preconditions for women to participate were program costs, and travel time not exceeding 15 min. Conclusions: From the perspective of postpartum women, there is room for improvement of preventive pelvic floor management. Further research should focus on strategies to tackle major barriers and to introduce facilitators for postpartum women to participate in PFMT programs.